Closed–loop oxygen usage during invasive mechanical ventilation of pediatric patients (CLOUDIMPP): a randomized controlled cross-over study - Atakul, Gulhan; Ceylan, Gokhan; Sandal, Ozlem; Soydan, Ekin; Hepduman, Pinar; Colak, Mustafa; Zimmermann, Jan M.; Novotni, Dominik; Karaarslan, Utku; Topal, Sevgi; Aǧin, Hasan (Frontiers in Medicine, 2024)
Background The aim of this study is the evaluation of a closed-loop oxygen control system in paediatric patients undergoing invasive mechanical ventilation (IMV). Methods Cross-over, multicenter, randomised, single-blind clinical trial. Patients between the ages of one month and eighteen years who were undergoing IMV therapy for acute hypoxemic respiratory failure (AHRF) were assigned at random to either begin with a two-hour period of closed-loop oxygen control or manual oxygen titrations.By using closed-loop oxygen control, the patients' SpO2 levels were maintained within a predetermined target range by the automated adjustment of the FiO2. During the manual oxygen titration phase of the trial, healthcare professionals at the bedside made manual changes to the FiO2, while maintaining the same target range for SpO2. Following either period, the patient transitioned to the alternative therapy. The outcomes were the percentage of time spent in predefined SpO2 ranges ±2% (primary), FiO2, , total oxygen use, and the number of manual adjustments. Findings The median age of included 33 patients was 17 (13–55.5) months. In contrast to manual oxygen titrations, patients spent a greater proportion of time within a predefined optimal SpO2 range when the closed-loop oxygen controller was enabled (95·7% [IQR 92·1–100%] vs 65·6% [IQR 41·6–82·5%]), mean difference 33·4% [95%–CI 24·5–42%]; P<0.001). Median FiO2 was lower (32·1% [IQR 23·9–54·1%] vs 40·6% [IQR 31·1–62·8%]; P<0.001) similar to total oxygen use (19·8 L/h [IQR 4·6–64·8] vs 39·4 L/h [IQR 16·8–79]; P<0.001); however, median SpO2/FiO2 was higher (329·4 [IQR 180–411·1] vs 246·7 [IQR 151·1–320·5]; P<0.001) with closed–loop oxygen control. With closed–loop oxygen control, the median number of manual adjustments reduced (0·0 [IQR 0·0–0·0] vs 1 [IQR 0·0–2·2]; P<0.001). Conclusion Closed-loop oxygen control enhances oxygen therapy in pediatric patients undergoing IMV for AHRF, potentially leading to more efficient utilization of oxygen. This technology also decreases the necessity for manual adjustments, which could reduce the workloads of healthcare providers. Clinical Trial Registration This research has been submitted to ClinicalTrials.gov (NCT05714527)